Archaeobotanical analyses of kitchen waste of Jever Castle, 17th/18th century - feature - Felix Bittmann (PANGAEA, 2023)
During restoration works in the castle of Jever, Lower Saxony, a hidden niche in the former kitchen wall was found filled-up with wate material: botanical remains, bones, insects, molluscs, bricks, mortar. The analysis revealed a large number of plant species both local and imported (Olea). In addition, bones of mammaly, birds, fishes and amphibia were identified.
In: Bittmann, F (2023): Archaeobotanical analyses of kitchen waste of Jever Castle, 17th/18th century [dataset bundled publication]. Niedersächsisches Institut für historische Küstenforschung, Wilhelmshaven, PANGAEA, https://doi.org/10.1594/PANGAEA.962169